Fundamentals and Advances in Stimuli-Responsive Hydrogels and Their Applications: A Review - Iryna S. Protsak; Yevhenii M. Morozov (Gels)
This review summarizes the fundamental concepts, recent advancements, and emerging trends in the field of stimuli-responsive hydrogels. While numerous reviews exist on this topic, the field continues to evolve dynamically, and certain research directions are often overlooked. To address this, we classify stimuli-responsive hydrogels based on their response mechanisms and provide an in-depth discussion of key properties and mechanisms, including swelling kinetics, mechanical properties, and biocompatibility/biodegradability. We then explore hydrogel design, synthesis, and structural engineering, followed by an overview of applications that are relatively well established from a scientific perspective, including biomedical uses (biosensing, drug delivery, wound healing, and tissue engineering), environmental applications (heavy metal and phosphate removal from the environment and polluted water), and soft robotics and actuation. Additionally, we highlight emerging and unconventional applications such as local micro-thermometers and cell mechanotransduction. This review concludes with a discussion of current challenges and future prospects in the field, aiming to inspire further innovations and advancements in stimuli-responsive hydrogel research and applications to bring them closer to the societal needs.